Entre lógicas cinegéticas y agrícolas: el chamanismo nahua en una cosmología de sacrificio - David Lorente Fernández (Journal de la Société des Américanistes)
Mesoamerican forms of shamanism have rarely been discussed in international academic debates. Through ethnographic information collected in the Sierra de Texcoco, in Mexico, what might be called a Nahua shamanic tradition is analyzed in light of the interlacing of relationship modes conceptually associated with hunting and agriculture. Nahua shamanism relates to a sacrificial cosmology that places predation as the first moment of a cosmic cycle of agonistic exchange, whose moment of retribution is linked to rain and agricultural fertility. The specificity of Nahua shamanism lies precisely in this articulation of logics of a hunting and agricultural nature, involved in the definition all at once of the entities at work, of the specialist himself and of the dynamics that govern the exercise of cosmic politics.